2017
DOI: 10.1007/s00262-017-2018-7
|View full text |Cite
|
Sign up to set email alerts
|

Decreased human leukocyte antigen A*02:01 frequency is associated with risk of glioma and existence of human cytomegalovirus: a case–control study in Northern China

Abstract: There is a correlation between decreased HLA-A*0201 allele frequency and glioma susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…In our previous study we detected IE1–72 immunoreactivity in 76.1% of malignant glioma specimens of various grades, and pp65 in 65.7%; no IE1–72- or pp65-positive cells were detected in control brain tissue specimens [11], a finding consistent with the results of Cobbs et al [7] and Mitchell et al [12]. However, in other studies [1822], no evidence of a direct association between malignancies and HCMV infection was found, and the association of HCMV with malignancies is still controversial, with conflicting reports in the literature [7–9, 16, 1832]. Whether HCMV plays a role in the tumor progression, or whether tumor growth simply provides a supportive environment for local reactivation and propagation of the virus, is also generally unclear.…”
Section: Discussionsupporting
confidence: 80%
“…In our previous study we detected IE1–72 immunoreactivity in 76.1% of malignant glioma specimens of various grades, and pp65 in 65.7%; no IE1–72- or pp65-positive cells were detected in control brain tissue specimens [11], a finding consistent with the results of Cobbs et al [7] and Mitchell et al [12]. However, in other studies [1822], no evidence of a direct association between malignancies and HCMV infection was found, and the association of HCMV with malignancies is still controversial, with conflicting reports in the literature [7–9, 16, 1832]. Whether HCMV plays a role in the tumor progression, or whether tumor growth simply provides a supportive environment for local reactivation and propagation of the virus, is also generally unclear.…”
Section: Discussionsupporting
confidence: 80%
“…Antibodies to HCMV IE1 (68-72-kDa protein) were used on 773 tumor samples from 21 studies. Samples were positive for HCMV IE1 in 14 studies [2,4,26,27,29,36,38,46,50,56,57,63,87] and negative in 7 [44,67,69,76,82,85,96]. In 389 of 773 samples (50.3%), HCMV IE1 proteins were detected with antibody clones E13 [87], 6F8.2 [4], or 8B1.2 [4,26,46]; in 13 studies, the clones were not specified [2,27,29,36,38,50,56,57,63,67,69,82,85].…”
Section: Hcmv Ie Protein Detectionmentioning
confidence: 99%
“…However, another recent study including Northern Chinese citizens showed decreased risk of glioma development in people with HLA-A*0201. Third, all but one study included only western populations (18). In this context, we sought to evaluate whether the polymorphism of HLA can affect the risk of GBM development in Koreans.…”
Section: Baseline Characteristics Of Gbm Patientsmentioning
confidence: 99%
“…A few studies have evaluated potential association between HLA polymorphism and risk of glioma; however, the results remain unclear (17)(18)(19)(20)(21)(22)(23)(24). Most studies used serologic methods, which resulted in only two-digit resolution of HLA genotypes (19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation